Smart city readiness in Malaysia: The role of HCI and UX - Ghazali, Masitah; Hussen, Idyawati; Mahmud, Murni; Md. Noor, Nor Laila (Asian HCI Symposium'18 on Emerging Research Collection, 2018)
Smart city is not just about equipping the city with sensors to collect and push electronic data to citizens for the sake of keeping in the trend of Internet of Things. What is far more important is to also equipping the citizens to become smart citizens. In this paper, we describe the journey of empowering the Malaysians citizens by considering HCI and UX, which is also a part of the bigger plan of the KL ACM Chapter, that is to provide an ecosystem of symbiotic collaborations between the academia, government agencies and industries.